2022
DOI: 10.12968/jowc.2022.31.sup3.s29
|View full text |Cite
|
Sign up to set email alerts
|

Paracrine effects of adipose-derived stem cells in cutaneous wound healing in streptozotocin-induced diabetic rats

Abstract: Objective: The purpose of this study was to explore the paracrine effects of adipose-derived stem cells (ASCs) on cutaneous wound healing in diabetic rats Method: The ASCs were isolated and identified by immunofluorescent staining. The ASCs-conditioned medium (ASCs-CM) was harvested. Cell counting kit (CCK)-8 assay, scratch experiments, western blot and quantitative polymerase chain reaction (qPCR) were performed to observe the effects of ASCs-CM on fibroblasts. A full-thickness skin wound diabetic rat model w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Recent findings demonstrate that stem cells have therapeutic capacity in healing chronic wounds [ 2 ]. Mesenchymal stem cells (MSCs), endothelial progenitor cells, and hematopoietic stem cells are involved in the wound healing process via direct or indirect mechanisms, such as transdifferentiation, re-epithelialization, paracrine actions, and remodeling of the extracellular matrix [ 3 , 4 , 5 ]. However, there are some controversies regarding the efficacy of stem cells in clinical trials [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent findings demonstrate that stem cells have therapeutic capacity in healing chronic wounds [ 2 ]. Mesenchymal stem cells (MSCs), endothelial progenitor cells, and hematopoietic stem cells are involved in the wound healing process via direct or indirect mechanisms, such as transdifferentiation, re-epithelialization, paracrine actions, and remodeling of the extracellular matrix [ 3 , 4 , 5 ]. However, there are some controversies regarding the efficacy of stem cells in clinical trials [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…32 ASC-conditioned medium can promote diabetic wound healing through increasing TGF-β1 secretion. 29 Consistently, TGF-β1, a key wound healing growth factor, is upregulated in wounds treated with ASCs loaded in Pluronic F-127 hydrogels. 21 We found that IL-6 levels decreased, macrophage polarization and promote angiogenesis to accelerate diabetic wound healing.…”
Section: Discussionmentioning
confidence: 93%
“…The combination of acupuncture and stem cell‐seeded cryogel/hydrogel biomaterials on wounds produces immunomodulatory effects, partially mediated by the reduced expression of proinflammatory cytokines (IL‐1β and TNF‐α) 32 . ASC‐conditioned medium can promote diabetic wound healing through increasing TGF‐β1 secretion 29 . Consistently, TGF‐β1, a key wound healing growth factor, is upregulated in wounds treated with ASCs loaded in Pluronic F‐127 hydrogels 21 .…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations